Modeling the Structure of Intellectual Means of Decision-Making Using a System-Oriented NFO Approach - M. Ayaz Ahmad; Tvoroshenko, I.; Jalal Hasan Baker; Lyashenko, V. (WARSE, 2019)
This article developed the structure of an intelligent decision-making system based on the constructed NFO-models, which demonstrated an increase in the effectiveness of decisions made in the medical diagnosis of some cardiovascular diseases. The presented architecture leads to the adoption of reliable decisions through the use of the verbal method of presenting data. This system uses existing approaches to formalization and diagnostics, conducts data mining, and provides the user with complete information for making a decision. Intelligent decision-making system can be used both in clinical practice by novice specialists, and in training students and doctors in continuing education institutions.
Keywords: Modeling; Structure; Intelligent System; Efficiency